2000
DOI: 10.1086/315740
|View full text |Cite
|
Sign up to set email alerts
|

Natural T, γδ, and NK Cells in Mycobacterial,Salmonella,and Human Immunodeficiency Virus Infections

Abstract: NK cells, gammadelta T cell antigen receptor chain-positive cells, and CD3(+)CD16/56(+) (natural T [NT]) cells are involved in innate immunity and immunoregulation; however, their role in clinical infection is not well defined. Cytofluorometric analysis was used to examine peripheral blood from bacteremic, nonbacteremic, and healthy human immunodeficiency virus (HIV)-positive and -negative persons in Malawi, Africa. Mycobacteremia was associated with a higher proportion of CD3(+)CD8(-) gammadelta cells (median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 24 publications
3
42
0
1
Order By: Relevance
“…NKT cells are involved in innate immunity and carry out the recognition of the antigens regardless of αβ T cells (15). In this study, a high percentage of NKT cells were detected in patients before the treatment.…”
Section: Cd25mentioning
confidence: 56%
“…NKT cells are involved in innate immunity and carry out the recognition of the antigens regardless of αβ T cells (15). In this study, a high percentage of NKT cells were detected in patients before the treatment.…”
Section: Cd25mentioning
confidence: 56%
“…These results are consistent with previous studies using bovine and human TCR␥␦ T cells that also showed that cytokine production and cell proliferation did not necessarily correlate (80,81). In contrast, activation of TCR␥␦ ϩ T cells by Mycobacterium tuberculosis Ags is dependent upon accessory cells, but is non-MHC restricted (42). However, small phosphoantigens of M. tuberculosis appear to be associated with larger carrier molecules that require processing to allow phosphate ligands to traffic from phagosomes to the cell surface for stable expression and presentation.…”
Section: Figure 6 Tcr␥␦mentioning
confidence: 99%
“…Increased numbers of peripheral blood TCR␥␦ T cells have been documented in a number of different bacterial infections (25,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Our results poise the important question of whether TCR␥␦ ϩ T cells are also elevated in the peripheral blood of leptospirosis patients.…”
Section: Figure 5 Preferential Expansion Of Tcr␣␤mentioning
confidence: 99%
See 1 more Smart Citation
“…We ourselves have rarely, if ever, noted spontaneous cytokine production in PBMCs of healthy U.S. blood donors (reference 7 and unpublished data). However, in a multicenter, multiphase study of the immune correlates of bloodstream infections in developing countries (8,10,11), we noticed individuals whose PBMCs produced cytokines without stimulation. Other researchers, measuring either protein or mRNA, have detected spontaneous cytokine production by bronchoalveolar lavage fluid cells of patients with asthma (4), interacting umbilical vein endothelial cells-monocyte cells (17), human milk mononuclear cells (20), peripheral blood lymphocytes of persons with atopic dermatitis (19,23), peripheral blood monocytes of patients with multiple sclerosis (3), or CD4 ϩ T cells of persons with active Mycobacterium tuberculosis pulmonary infection (2).…”
mentioning
confidence: 95%